The metal-insulator transition in the paramagnetic Hubbard Model - Miranda, E.; García, D. J.; Hallberg, Karen Astrid; Rozenberg, Marcelo Javier (Elsevier Science, 2008)
Fil: Miranda, E.. Universidade Estadual de Campinas; Brasil